Trastuzumab treatment after progression in HER2-positive metastatic breast cancer following relapse of trastuzumab-based regimens: a meta-analysis - Han, Yiqun (Cancer Manag Res, 2019)
Background: This meta-analysis assessed the safety and effectiveness of retreatment with trastuzumab in patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (HER2+MBC). Materials and methods: Randomized controlled trials (RCTs) and cohort studies that compared the clinical outcomes of continuation and termination of trastuzumab treatment in HER2+MBC after failure of trastuzumab-based regimens were analyzed. Pooled estimates of time to progression (TTP) survival, overall survival (OS), the incidence of adverse events and central nervous system (CNS) perturbations were determined. Results: Four RCTs and six cohort studies with 2,409 patients were identified. The continuation of trastuzumab presented a statistical significance in prolonging TTP (HR 0.88; 95% CI: 0.82–0.94; P<0.000) and OS (HR 0.87; 95% CI: 0.82–0.93; P<0.000). Furthermore, retreatment with trastuzumab did not add to the risk of cardiac events (relative risk, 2.48; 95% CI: 0.86–7.15) or the incidence of CNS metastasis (P=0.83). Conclusion: Our findings confirm the clinical benefits and safety of retreatment therapy with trastuzumab for HER2-positive patients with metastatic cancer of the breast that had progressed during trastuzumab-based treatment regimens.